Emergency contraception using progestin drugs in domestic cats - A. Vasetska (Ukrainian Journal of Veterinary and Agricultural Sciences, 2020)
Today, in conditions of strict quarantine, when it is not always possible to carry out surgery in cats, some methods of emergency drug contraception can be used. Over the years, many contraceptive medications have been developed for companion animals, but many secondary adverse effects have limited their use. However, in all species, the secondary adverse effects of progesterone-type drugs limit their use and vary depending on when treatment is given in relationship to the stage of the estrous cycle. An ideal non-surgical sterilant would be safe, effective, permanent, administered as a single injection and capable of being manufactured inexpensively. Contraceptives are used for cats, as a method of renewable fertility over time for breeding animals, as a method of suppressing sexual function for animals at risk for surgery, and to prevent over populations in stray cats. The use of non-surgical, safe and effective methods of suppression of sexual function in cats eliminates traumatization, anesthesia and complicated postoperative period in animals, which in some cases are impossible in the state of health, etc. The most common and affordable method of medical contraception is progestins, such as megestrol acetate, medroxyprogesterone acetate, proligestone (used orally or as a depot injection). These drugs are effective in inhibiting sexual function. Contraceptives for felids are available as implants, depot injections, and pills or liquid for oral administration, powder for mixing with food, or as vaccines. Regimens may differ according to the timing of first treatment, whether coinciding with the active reproductive period, preceding this period, or during anestrus. Ideally, the treatment regimen is initiated during anestrus to minimize the dose needed for reproductive suppression and to avert exposure to endogenous steroids that can cause lesions in reproductive organs.